1985
DOI: 10.1002/jcp.1041230321
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transport system A and N amino acids and of nerve and epidermal growth factors on the induction of ornithine decarboxylase activity

Abstract: The induction of ornithine decarboxylase (EC 4.1.1.17) (ODC) by amino acids and by the peptide hormones nerve growth factor (NGF) and epidermal growth factor (EGF) in salts-glucose media has been studied. Only those neutral amino acids taken into the cell via one of the Na+ dependent transport systems stimulate ODC activity. Asparagine and the nonmetabolizable alpha-amino-isobutyric acid (AIB) were used as representatives of this class of inducing amino acids, and their intracellular concentrations were relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Since a-aminoisobutyric acid is a nonmetabolizable amino acid, the induction of ornithine decarboxylase activity is not due to the participa-* tion of a-aminoisobutyric acid in protein synthesis or to other reactions involving covalent modification of a-amino-0 isobutyric acid. (21). The of 0.1 AM insulin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since a-aminoisobutyric acid is a nonmetabolizable amino acid, the induction of ornithine decarboxylase activity is not due to the participa-* tion of a-aminoisobutyric acid in protein synthesis or to other reactions involving covalent modification of a-amino-0 isobutyric acid. (21). The of 0.1 AM insulin.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular association becomes more interesting in the light of the fact s trichloroacetic acid-soluble radioobtained with the nonmetabolizable that the ornithine decarboxyelase-inducing amino acids are log, a-aminoisobutyric acid. o, transported via Na+-dependent transport systems (21). e with insulin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent studies it was shown that nonmetabolizable analogs of the group 'A' amino acids also elevate ODC (Viceps-Madore et al, 1982). These investigators further reported that amino acids that are transported through a Na+-dependent cotransport system must be present in EBSS for CAMP, epidermal growth factor, and nerve growth factor to enhance ODC expression (Rinehart et al, 1985). These results suggested that ODC induction might be linked to the transport system of some amino acids.…”
Section: Discussionmentioning
confidence: 92%
“…Ornithine decarboxylase activity in various cell types is induced by specific amino acids (Rinehart et al, 1985). In mouse neuroblastoma cells, the most potent inducers are asparagine, glutamine, and serine.…”
Section: Atp Content Does Not Change In Cells Protected By Amino Acidmentioning
confidence: 99%